Fracture detection in X-ray images of long bone - Gajjar, B; Patel, S; Vaghela, A (International Journal of Computer Sciences and Engineering, 2025)
Image processing used in wide variety of applications such as Image restorations, satellite, and medical etc. With enrichments of the image processing libraries especially of openCV and Matlab, many applications are being developed day by day in computer vision or image processing domain. We have designed the bone fracture detection method using “Image Processing” toolbox in Matlab. Aim of the project is to locate exact fracture area in inputted X-ray image. We will check bone integrity to detect any crack or disjoint of two cartilages. The professed algorithm is divided in few step namely pre-processing, Segmentation and ROI search and detection. Features like area, length and pixel locations of the segments are used to identify fracture in X-ray image. Algorithm has been simulated on various X-ray images which show good results to locate fracture in image. Also, in this approach we found that canny edge detection works far better than any other edge detection for segmenting the fractured part.